2011
DOI: 10.1158/0008-5472.can-11-1801
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Immunoregulator SRA/CD204 Potentiates Specific Dendritic Cell Vaccine-Induced T-cell Response and Antitumor Immunity

Abstract: Although dendritic cell (DC) vaccines offer promise as cancer immunotherapy, further improvements are needed to amplify their clinical therapeutic efficacy. The pattern recognition scavenger receptor SRA/CD204 attenuates the ability of DCs to activate CD8+ T cell responses. Therefore, we examined the impact of SRA/CD204 on antitumor responses generated by DC vaccines and we also evaluated the feasibility of enhancing DC vaccine potency by SRA/CD204 blockade. DCs from SRA/CD204 deficient mice were more immunoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 34 publications
(46 reference statements)
1
52
0
Order By: Relevance
“…For instance, nanoparticle-Ag complexes are efficiently taken up by DCs (49). Downregulation of SRA/CD204, a pattern recognition scavenger receptor, strongly enhances DC-mediated antitumor immunity (50). We have shown that increased AZI2 expression in GMDCs significantly enhanced the efficacy to activate CD4 + T cells in vivo.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, nanoparticle-Ag complexes are efficiently taken up by DCs (49). Downregulation of SRA/CD204, a pattern recognition scavenger receptor, strongly enhances DC-mediated antitumor immunity (50). We have shown that increased AZI2 expression in GMDCs significantly enhanced the efficacy to activate CD4 + T cells in vivo.…”
Section: Discussionmentioning
confidence: 85%
“…Our proof-of-principle studies demonstrate that downregulation of SRA in DCs enhances the immunostimulatory activity of a DC vaccine (157). We show that SRA-silenced DCs carrying melanoma antigen gp100 are more efficient than controls in mobilizing antigen-specific CTLs, leading to improved control of established melanoma and its metastases.…”
Section: Hsp110 and Grp170-binding Receptors And Vaccine Designmentioning
confidence: 84%
“…We show that SRA-silenced DCs carrying melanoma antigen gp100 are more efficient than controls in mobilizing antigen-specific CTLs, leading to improved control of established melanoma and its metastases. This enhanced antitumor efficacy correlates positively with greater tumor-infiltrating CD8 + T cells and NK cells, as well as increased intratumoral ratios of effector T cells to regulatory T cells (157). In addition, in situ administration of SRA-silenced DCs enhances the effectiveness of local radiotherapy by provoking a robust systemic antitumor immunity (158).…”
Section: Hsp110 and Grp170-binding Receptors And Vaccine Designmentioning
confidence: 99%
“…30 The scavenger receptors, CD163 and CD204, are also expressed by DC subsets in some species. 43,87 Expression patterns of CD163 and CD204 in normal canine DCs have not been reported. Of the markers mentioned, only CD11b is not assessable in formalin-fixed tissues.…”
Section: Histiocytic Diseases Of Interstitial DC and Macrophage Originmentioning
confidence: 99%